Utilization-Focused Evaluation (U-FE) Checklist - and Patton, Michael Quinn (The Evaluation Center, 2013)
Utilization-Focused Evaluation begins with the premise that evaluations should be judged by their utility and actual use; therefore, evaluators should facilitate the evaluation process and design any evaluation with careful consideration of how everything that is done, from beginning to end, will affect use. Use concerns how real people in the real world apply evaluation findings and experience and learn from the evaluation process. The checklist is based on Essentials of Utilization-Focused Evaluation (Patton, 2012, Sage Publications). All references in the checklist to exhibits and menus refer to this book. Step 1 Assess and build program and organizational readiness for utilization-focused evaluation. Step 2 Assess and enhance evaluator readiness and competence to undertake a utilizationfocused evaluation. Step 3 Identify, organize, and engage primary intended users. Step 4 Conduct situation analysis with primary intended users Step 5 Identify primary intended uses by establishing the evaluation’s priority purposes. Step 6 Consider and build in process uses if appropriate. Step 7 Focus priority evaluation questions. Step 8 Check that fundamental areas for evaluation inquiry are being adequately addressed. Step 9 Determine what intervention model or theory of change is being evaluated. Step 10 Negotiate appropriate methods to generate credible findings and support intended use by intended users. Step 11 Make sure intended users understand potential controversies about methods and their implications. Step 12 Simulate use of findings. Step 13 Gather data with ongoing attention to use. Step 14 Organize and present the data for use by primary intended users. Step 15 Prepare an evaluation report to facilitate use and disseminate significant findings to expand influence. Step 16 Follow up with primary intended users to facilitate and enhance use. Step 17 Metaevaluation of use: Be accountable, learn, and improve